THE RELATIONSHIP BETWEEN SUPPORT OF HUSBAND AND HEALTH OFFICERS AND HIV TESTING IN PREGNANT MOTHERS IN KENDARI CITY HEALTH CENTRE: HIV TESTING IN PREGNANT MOTHERS - Asri Dewi; Timbul Supodo; Kartini Kartini (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2022)
Background: A preliminary survey conducted by interviewing 10 (ten) pregnant women at Kendari City Health Center found that as many as 6 (six) people did a pregnancy check but did not take the human immunodeficiency test at the health centre  on the grounds that the mother could not be infected with HIV and AIDS because they have sexual relations only with their husbands and 4 (four) pregnant women take an HIV test because it is recommended by the midwife to do an HIV test. HIV. Methods: This  quantitative research used cross sectional study design. The population is 703 pregnant women, with the determination of the sample usingLemeshow formula so that the number of samples is 85 pregnant women. Result: Statistical test showed that the value (X2hits)= 12,117 > X2tabs=3,841, for the relationship between husband's support and examination of human immunodeficiency virus in pregnant women and (X2hits)= 14,859> X2tabs=3,841, for the relationship between the support of health workers and the examination of human immunodeficiency virus in pregnant women in the Kendari City Health Center Work Area. Conclusion: There is a relationship between husband's support and health workers with examination of human immunodeficiency virus in pregnant women in the Kendari City Health Center Working Area